2021
DOI: 10.1080/17470919.2021.1970016
|View full text |Cite
|
Sign up to set email alerts
|

Father-child dyads exhibit unique inter-subject synchronization during co-viewing of animation video stimuli

Abstract: Inter-subject synchronisation reflects the entrainment of two individuals to each other's brain signals during passive joint tasks. Within the parent-child dyad, the temporal coordination of signals indicates an attunement to each other's emotional states. Despite the ubiquity with which parents and their children watch screen media together, no study has investigated intersubject synchronisation in father-child dyads during such a co-viewing activity. The present study examined whether father-child dyads woul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…The second study (Father-Child synchrony study) consists of fNIRS recordings of Fathers and Children engaging in both a passive video viewing task and an active play task. Only data from fathers (N = 29, Mean Age = 38.1 ± 3.67) have been selected for the current dataset [20].…”
Section: Datasetmentioning
confidence: 99%
“…The second study (Father-Child synchrony study) consists of fNIRS recordings of Fathers and Children engaging in both a passive video viewing task and an active play task. Only data from fathers (N = 29, Mean Age = 38.1 ± 3.67) have been selected for the current dataset [20].…”
Section: Datasetmentioning
confidence: 99%
“…Recently, researchers have begun to investigate inter-brain synchrony between parents and infants and between parents and young children. They reported that inter-brain synchrony increases during cooperative conditions (Reindl et al, 2018;Miller et al, 2019;Nguyen et al, 2021a), during holding infant (Minagawa et al, 2018), during free play with mutual gaze (Piazza et al, 2020), when engaging in verbal turn-taking conversations (Nguyen et al, 2021b), and during joint-watching of movie stimuli (Azhari et al, 2021). These studies support the view that neural synchrony between parents and children may play a key role in the development of social ability.…”
Section: Introductionmentioning
confidence: 69%
“…Mothers’ parenting stress 23 has been found to be associated with reduced brain-to-brain synchrony; and an exploratory study suggests that mothers’ attachment anxiety might also influence brain coupling 53 . Synchrony in father-child dyads was also found during the video stimulation session 54 , possibly associated with father age and parenting experience. When analysing group-level neural activation between mothers and children, asymmetric brain response was found in mothers compared to children when mutual gaze occurred during the play session 55 , where mothers demonstrated PFC deactivation while children showed an activation, implying divergent PFC mechanisms even though dyads are engaged in symmetrical behaviours such as mutual gaze.…”
Section: Technical Validationmentioning
confidence: 85%